Structural and conductivity studies of polyacrylonitrile/methylcellulose blend based electrolytes embedded with lithium iodide - Nadirah, B.N. (Elsevier Ltd, 2020)
Two polymer electrolyte systems consisting of polyacrylonitrile (PAN)-methylcellulose (MC) blend have been prepared using solution cast technique. For undoped material, polymer blend based films have been prepared at various PAN-MC ratios. The hydrogen bonding interaction between the two polymers is analyzed using Fourier transform infrared spectroscopy (FTIR). PAN-MC interaction is proven from the shifting of CtbndN and OH stretching band. The undoped films have been examined using X-ray diffraction (XRD) technique to determine the most amorphous film. The blend of 50 wt.% PAN and 50 wt.% MC has been found as the most amorphous and served as the polymer host. Thermogravimetric analysis (TGA) is used to study the thermal stability of PAN, MC and PAN-MC blend films. It is revealed that PAN-MC film is thermally stable up to ~330 Â°C. In PAN-MC-LiI section, the complexation between the polymer host and lithium iodide (LiI) is confirmed using FTIR analysis. From XRD studies, the degree of crystallinity of PAN-MC based electrolytes is found to decrease with the incorporation of LiI up to 50 wt.%. Impedance spectroscopy technique is performed to study the effect of LiI on the conductivity and other electrical properties of electrolytes. Â© 2020 Hydrogen Energy Publications LLC